2018
DOI: 10.1016/j.cviu.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

3D non-rigid registration using color: Color Coherent Point Drift

Abstract: Research into object deformations using computer vision techniques has been under intense study in recent years. A widely used technique is 3D non-rigid registration to estimate the transformation between two instances of a deforming structure. Despite many previous developments on this topic, it remains a challenging problem. In this paper we propose a novel approach to non-rigid registration combining two data spaces in order to robustly calculate the correspondences and transformation between two data sets.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Therefore, the objective function of point set registration was composed of the global distance item, non-rigid transformation constraint item and two local structure constraints items.Extraction the feature of point sets: The spatial location of point sets is a traditional feature for registration. In [86], the color information of point sets was used to extend the CPD algorithm. In [87], the correlation of color information and spatial location information was formulated.…”
Section: Pairwise Point Set Registrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the objective function of point set registration was composed of the global distance item, non-rigid transformation constraint item and two local structure constraints items.Extraction the feature of point sets: The spatial location of point sets is a traditional feature for registration. In [86], the color information of point sets was used to extend the CPD algorithm. In [87], the correlation of color information and spatial location information was formulated.…”
Section: Pairwise Point Set Registrationmentioning
confidence: 99%
“…Then, an expectation-maximization (EM) algorithm is applied to perform this ML optimization. Many algorithms were proposed to extend the CPD method [ 1 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. These algorithms can be summarized as follows: Selecting a suitable non-rigid transformation function: In the CPD method, only one non-rigid transformation function is considered.…”
Section: Pairwise Point Set Registrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantage of ICP-based methods is their scalability to large point sets, and variants of the ICP algorithm have been developed in the field of mesh registration [5], [6], [7], [8], [9]. The latter group comprises the registration methods in which point-to-point correspondences are assumed to be one-to-many, and this characteristic often contributes to their robustness [10], [11], [12], [13], [14], [15], [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have reported CPD variants seeking to optimally assign the GMM membership probability using rotation invariant shape descriptors [23], correspondence priors and correspondence preserving subsampling approaches [24], and the shape context of one point with respect to the distribution of other points [25]. On the other hand, Saval-Calvo et al [26] proposed color-CPD algorithm to register 3D points by using color and shape spaces to jointly estimate the best match.…”
Section: Introductionmentioning
confidence: 99%